PENGARUH PELAYANAN PRIMA TERHADAP KEPUASAN PELANGGAN DI JADE BAMBOO RESTO YOGYAKARTA - Fadilah Hasanah (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2016)
ge-newline"> This study aimed to describe (1) excellent service, (2) curtomers’ satisfaction, and (3)the influence of excellent service toward curtomers’ satisfaction. This study was ex-post facto.Data colleting methods used questionnairesand documentation. Data analyzing methodsused descriptive analysis and hypothesis testingby using Product Moment that was started bynormality and linearity test. This study showsthat excellent service was in high category withthe relative frequency 54.55% and curtomers’satisfaction was in high category with relativefrequency 53.25%. Based on the result of Product Moment, the score of rxy was 0,448. Thescore of r table in the significant level 5% fortotal respondents 77 was 0.227 (rxy 0,448 > rtable 0.227). It could be stated there was a positive and significant influence of excellent service toward curtomers’ satisfaction. The determinant coefficient (R2) was 0.201, it means thatexcellent service gave contribution for about20.1% toward curtomers’ satisfaction, while79.9% was influenced by other factors thatwere not discussed in this study; they werequality, price, service, facilities of the product,and easiness of customers’ sasfacon.